PENGEMBANGAN BAHAN AJAR TERSTRUKTUR UNTUK MENINGKATKAN KETERAMPILAN MAHASISWA DALAM MERANCANG MEDIA HANDS ON ACTIVITY SERTA LEMBAR KERJA EKSPLORATIF PENDAMPING - Indhira Asih Vivi Yandari; Hepsi Nindiasari; Etika Khaerunnisa; Aan Subhan Pamungkas (Universitas Sultan Ageng Tirtayasa, 2018)
ABSTRACTThis research is motivated by the lack of ability of student teachers of mathematics FKIP University of Sultan Ageng Tirtayasa in developing worksheets and media exploratory hands on activity. Based on observations in the course clump of learning (planning, strategies and evaluation) and the implementation of microteaching done by the students, obtained the fact that students in developing a worksheet is a collection of questions and do not require the capability of understanding the concept of the student. In addition, student teachers are still rarely use the media in learning, due to difficulties in designing and creating instructional media. Hence the need for teaching material that can be used as guides student teachers to develop explorative and media worksheet hands on activity. Thus the formulation of the problem and the purpose of this study is how to develop teaching material based worksheets and media exploratory hands on activity. The method used in this research is the development method includes preliminary studies, draft development, testing and development of the final product.The results of this research is a module consisting of four units, units of learning theory, the difference unit worksheets and job sheets, media unit hands on activity and worksheet exploratory unit. In each unit consists of several sub-units that correspond to the unit. Based on the results of expert testing and limited trials showed that the worksheet-based development modules exploratory and hands on activity worthy of media used. Keywords: Teaching Material, Worksheet Explorative, Media Hands on Activuty